2006
DOI: 10.1097/01.ccm.0000215114.46127.da
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a T-piece system and a continuous positive airway pressure system for apnea testing in the diagnosis of brain death*

Abstract: The T-piece and the CPAP systems are effective alternatives to the standard oxygen catheter technique for apnea testing. Oxygenation was best maintained with the CPAP system, which can be useful in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 20 publications
2
38
1
3
Order By: Relevance
“…Tpiece systems used to provide oxygen via standard corrugated tubing connected to 100% oxygen at a flow of 12 L/ min have been shown to be as effective as the previously described oxygen cannula technique. 19 This method of apnea testing may theoretically be safer than the intratracheal catheter method, since the possible risk of increased intrathoracic pressure or pneumothorax would be lower. The investigators further modified their T-piece approach with corrugated tubing technique, with a 10 cm H 2 O CPAP valve attached to the distal extremity of the T-piece extension to enhance oxygenation.…”
Section: Methods Of Performing Apnea Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Tpiece systems used to provide oxygen via standard corrugated tubing connected to 100% oxygen at a flow of 12 L/ min have been shown to be as effective as the previously described oxygen cannula technique. 19 This method of apnea testing may theoretically be safer than the intratracheal catheter method, since the possible risk of increased intrathoracic pressure or pneumothorax would be lower. The investigators further modified their T-piece approach with corrugated tubing technique, with a 10 cm H 2 O CPAP valve attached to the distal extremity of the T-piece extension to enhance oxygenation.…”
Section: Methods Of Performing Apnea Testingmentioning
confidence: 99%
“…The investigators further modified their T-piece approach with corrugated tubing technique, with a 10 cm H 2 O CPAP valve attached to the distal extremity of the T-piece extension to enhance oxygenation. 19 Additional methods that allow the patient to stay connected to a mechanical ventilator circuit until the final phase of the apnea testing have been described. In one method, hypoventilation is achieved by reducing the minute ventilation to a low level and keeping the patient on the ventilator until the required PaCO 2 is attained.…”
Section: Methods Of Performing Apnea Testingmentioning
confidence: 99%
“…ETT/O 2 C ratio was calculated by dividing an internal diameter of ETT with an external diameter of O 2 C. Twelve kinds of ETT/O 2 C ratio were resulted with this formulation. Other variables Levésque et al 2006). In the hypoventilation and CPAP methods the patient is not disconnected from mechanical ventilator but minute ventilation volue is reduced to a very low level such as 0.5 -2 L min −1 (Lang and Heckmann 2005) or ventilation mode is changed to CPAP mode with 100% O 2 (Levésque et al 2006), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Apnea testing could be completed in all patients with the additional use of a CPAP valve. 27 Two studies have suggested monitoring of the apnea test with transcutaneous carbon dioxide partial pressure monitoring. However, comparison with predicting PCO 2 rise using an estimated 3 mm Hg increase per minute has not been performed.…”
Section: Analysis Of Evidencementioning
confidence: 99%